Improved branch and bound method for control structure screening - Cao, Yi; Saha, Prabirkumar (Elsevier Science B.V., Amsterdam., 2005)
The main aim of this paper is to present an improved algorithm of “Branch and Bound” method for control structure screening. The new algorithm uses a best- first search approach, which is more efficient than other algorithms based on depth-first search approaches. Detailed explanation of the algorithms is provided in this paper along with a case study on Tennessee–Eastman process to justify the theory of branch and bound method. The case study uses the Hankel singular value to screen control structure for stabilization. The branch and bound method provides a global ranking to all possible input and output combinations. Based on this ranking an efficient control structure with least complexity for stabilizing control is detected which leads to a decentralized proportional contr
Keywords: Control structure screening; Branch and bound method; Hankel singular value; Tennessee–Eastman process; Process control; Stability; Systems engineering; Optimization